Joyful noise : poems for two voices - Fleischman, Paul.; Beddows, Eric, 1951- ([New York] : HarperTrophy, 1988)
A collection of poems describing the characteristics and activities of a variety of insects.
"A Charlotte Zolotow book.".
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
Book Links (A.L.A.), August 2001.
Booklist, February 2005.
Keywords: Children's poetry, American; Insects -- Juvenile poetry; American poetry; Insects -- Poetry; American poetry; Insects -- Poetry